Congenital Mesoblastic Nephroma: Case Report: Nefroma mesoblástico congénito: reporte de caso - Paz Soldán Mesta, Carolina F. (2022)
Congenital mesoblastic nephroma (CMN) is the most frequent renal tumor in newborns and infants. under 3 months. The clinical case of a patient younger than 3 months, with prenatal diagnosis, referred in a timely manner for evaluation and management by the Institution is presented. CMN is a low incidence tumor. Early diagnosis as well as complete excision of the tumor are predictors of good prognosis, as in the case of our patient.